Pornografi dan Pengasuhan Anak: Menganalisis Dampak Media Digital terhadap Peran Keluarga dan Perkembangan Anak - Sinta; Asbari, Masduki; Isnawati, Bella (AGUSPATI RESEARCH INSTITUTA, 2024)
This study aims to address the issue of zina and pornography consumption among children by analyzing the impact of digital media. The study utilized a descriptive qualitative method, gathering data through oral narratives from a Youtube channel called Parenting Rumah Keluarga Risman. The findings suggest that in today's society, where technology and information are easily accessible, parents play a crucial role in protecting their children from exposure to pornography and adultery as a lifestyle. The research was motivated by the increasing number of unethical sexual cases involving both adults and children in Indonesia. The study highlights the unconscious change in behavior and perspective that can occur due to digital media exposure. As a result, there is a need for comprehensive education and legal measures to protect children from negative influences and mitigate the adverse impacts in this digital era.